Performance Optimization of Polymer Solar Cells Using Electrostatically Sprayed Photoactive Layers - Kim, Joon-Sung; Chung, Won-Suk; Kim, Kyungkon; Kim, Dong Young; Paeng, Ki-Jung; Jo, Seong Mu; Jang, Sung-Yeon (WILEY-V C H VERLAG GMBH, 2010)
Polymer solar cells (PSCs) are fabricated using a novel film deposition method, the electrostatic spray (e-spray) technique. Stable atomization and uniform deposition of the polymer blend by e-spray are achieved by manipulating the solution concentration, the solvent composition, and the electric field. The performance of PSCs is primarily influenced by the inherent film morphology of the e-sprayed polymer-blend active layers, which is significantly different from that of the conventional films that are formed using the spin-coating (SC) method. The intrinsically formed interfacial boundaries between the e-sprayed blend pancakes resist charge transport, which unfavorably influences device efficiency. The internal series resistance (R(S)) of the PSCs that are formed using the e-spray method (e-spray-PSC) is significantly reduced by a solvent vapor soaking (SVS) treatment in addition to the conventional thermodynamic nanomorphology controls. The detailed relationship between the morphologies (film morphology and internal nanomorphology) and the R S is revealed using impedance spectroscopy. The performance of the e-spray-PSCs is comparable to those of the PSCs that are fabricated using the SC method under identical conditions. Therefore, the e-spray method can be used to fabricate ultralow-cost PSCs, because of the performance results combined with the intrinsic advantages that the e-spray method is simple and has a low materials loss.